“Home is where the smart is”? Evaluating smart home research and approaches against the concept of home - Gram-Hanssen, K; Darby, S (Elsevier, 2017)
This article develops concepts of what the home is and reflects on smart home technology and the research literature on smart homes in relation to these concepts. The focus is on the aspects of smart home technologies related to energy management within the home (end-uses) and at network or grid level (system). Four aspects of a home are distinguished: a place for security and control, for activity, for relationships and continuity, and for identity and values. These aspects of home are used to discuss approaches to, and ideas of, the smart home, as reflected in the research literature. It is shown that technical and ‘prospective’ research literature focuses on aspects of security and control in the home as well as on activities, whereas research papers that are more conceptual and evaluative are more likely to include questions of relations, values and identities. The paper concludes that a broader understanding of the home in all aspects is needed when conducting research into smart homes. This can be valuable when evaluating how smart home technologies work in real homes, as well as in the more technical and prospective approaches to developing new socio-technical configurations.